Strategic Communication in Politics : Griffin’s Rhetoric Theory on Bobby Nasution’s Campaign - Olga Wansyan; Olvi Prihutami Sihombing; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to analyze Bobby Nasution’s campaign speech using Aristotle’s rhetorical proofs and Griffin’s Theory of Strategic Communication. The study investigates rhetorical proofs of logos, ethos, and pathos and explores their application in political communication. This qualitative research utilized content analysis with data derived from the transcript and video of Bobby Nasution’s speech, titled "Bobby Nasution Janji Prioritaskan Kesehatan dan Penanganan Hukum jika Menang Pilgub Sumut," uploaded on the YouTube channel Official iNews. The findings reveal that Bobby Nasution employed rhetorical proofs with a distribution of logos (37%), ethos (42%), and pathos (21%). Ethos was further demonstrated through practical wisdom (phronesis), moral virtue (arete), and goodwill (eunoia). Additionally, the speech balanced emotional appeals such as anger versus calmness and fear versus confidence to connect with the audience. This research contributes to the study of rhetoric by highlighting the importance of strategic communication in political campaigns and its relevance to audience engagement